Interleukin (IL)-17-producing pathogenic T lymphocytes co-express CD20 and are depleted by rituximab in primary Sjögren's syndrome: a pilot study. (3rd March 2016) - Alunno, A; Carubbi, F; Bistoni, O; Caterbi, S; Bartoloni, E; Di Benedetto, P; Cipriani, P; Giacomelli, R; Gerli, R
Summary: Compelling evidence suggests that interleukin (IL)-17 and IL-17-producing cells play a pivotal role in the pathogenesis of primary Sjögren's syndrome (pSS). We investigated phenotypical and functional effects of the anti-CD20 antibody rituximab (RTX) on circulating and glandular IL-17-producing T cells in pSS. RTX is able to deplete glandular IL-17 + CD3 + CD4 – CD8 – double-negative (DN) and CD4 + Th17 cells as well as circulating IL-17 + DN T cells. A fraction of glandular and circulating IL-17 + DN cells and CD4 + T helper type 17 (Th17) cells co-expresses CD20 on the cell surface explaining, at least in part, such depletive capacity of RTX. The exposure to RTX does not rescue the in-vitro corticosteroid resistance of IL-17 + DN T cells. Our results support further the therapeutic role in pSS of RTX that, despite its B cell specificity, appears able to also hamper IL-17-producing T cells in this disease.